2022
DOI: 10.1371/journal.pone.0264811
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tuberculosis incidence and the effects of multiple deprivation indices on tuberculosis management in OR Tambo district over a 5-year period

Abstract: Background This study investigated the associations between socio-economic deprivation and tuberculosis (TB) treatment outcomes, alongside well-known TB risk factors. The effects of healthcare expenditures and their growth on trends in TB incidence from 2009 to 2013 were also assessed. Methods Secondary data analysis was performed on data obtained from various sources including governmental, non-governmental and research institutions. Indicators for TB treatment outcomes included TB death rate, TB rate among… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Such obstacles could exist at the facility and health system levels and include a lack of specific instructions on which service is to be integrated in which department and how; insufficient supervisory on integrated training; and stock-outs of TB resources including drugs and ARVs supplier [29,30]. If clients believe that integrated services require lengthy wait times, poor privacy, and little opportunity for questioning during consultations, integration may be less beneficial from their perspective [31].…”
Section: Discussion: Creation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such obstacles could exist at the facility and health system levels and include a lack of specific instructions on which service is to be integrated in which department and how; insufficient supervisory on integrated training; and stock-outs of TB resources including drugs and ARVs supplier [29,30]. If clients believe that integrated services require lengthy wait times, poor privacy, and little opportunity for questioning during consultations, integration may be less beneficial from their perspective [31].…”
Section: Discussion: Creation Of the Modelmentioning
confidence: 99%
“…This is a potentially effective model for SA to address the high prevalence of HIV, TB, and HIV-TB coinfections, as well as limited human resources [4]. Although this is not the first empirical discussion of TB-HIV integration in South Africa, it is, as far as we know, the first attempt to examine operational issues of TB-HIV integration from the perspective of nurses at the facility level [26][27][28][29][30][31]. This paper describes the development of a district-based model for comprehensive and integrated TB and HIV care that meets the needs of the region.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the term eigenvalue can be termed as characteristic value, characteristic root, proper values or latent roots as well [32] Canonical discrimination Analysis (CDA): It builds a predictive model for group membership. One primary purpose of CDA is to separate classes (populations) in a lower dimensional discriminant space [32]. Mahalanobis distance: It is the distance of the test point from the centre of mass divided by the width of the ellipsoid in the direction of the test point.…”
Section: Definition Of Operational Conceptsmentioning
confidence: 99%
“…Mahalanobis distance: It is the distance of the test point from the centre of mass divided by the width of the ellipsoid in the direction of the test point. It can be used to determine whether a sample is an outlier, whether a process is in control or whether a sample is a member of a group or not [32] Posthoc analysis: Post hoc in Latin means 'after this'. Simply put, a post-hoc analysis refers to a statistical analysis specified after a study has been concluded and the data collected.…”
Section: Definition Of Operational Conceptsmentioning
confidence: 99%
See 1 more Smart Citation